1-dimensional TiO2 nano-forests as photoanodes for efficient and stable perovskite solar cells fabrication. (May 2017) - Salado, Manuel; Oliva-Ramirez, Manuel; Kazim, Samrana; González-Elipe, Agustín R.; Ahmad, Shahzada
Abstract: During the last years, perovskite solar cells have gained increasing interest among the photovoltaic community, in particularly after reaching performances at par with mature thin film based PV. This rapid evolution has been fostered by the compositional engineering of perovskite and new device architectures. In the present work, we report the fabrication of perovskite solar cells based on highly ordered 1-dimensional vertically oriented TiO2 nano-forests. These vertically oriented porous TiO2 photoanodes were deposited by physical vapor deposition in an oblique angle configuration, a method which is scalable to fabricate large area devices. Mixed (MA0.15 FA0.85 )Pb(I0.85 Br0.15 )3 or triple cation Cs0.05 (MA0.15 FA0.85 )0.95 Pb(I0.85 Br0.15 )3 based perovskites were then infiltrated into these 1-dimensional nanostructures and power conversion efficiencies of 16.8% along with improved stability was obtained. The devices fabricated using 1D-TiO2 were found to be more stable compare to the classical 3-dimensional TiO2 photoanodes prepared by wet chemistry. These 1-D photoanodes will be of interest for scaling up the technology and in other opto-electrical devices as they can be easily fabricated utilizing industrially adapted methodologies. Graphical abstract: Highlights: Template free large area uniform 1-directional TiO2 . Highly uniform Nano-forests like TiO2 structures. Facile charge collection and lower losses due to 1-D TiO2 structures. Triple cation based perovskite in conjugation with these 1-D TiO2 structures allowed highly efficient and stable perovskite solar cells fabrication.